Magyar egyetemalapítási kísérlet Kolozsváron 1920-ban - Vincze, Gábor (Közép-Európai Közlemények, 2009)
On the 24th of December in 1918 the Romanian army marched in the capital of Transylvania, Kolozsvár/Cluj - inhabited mostly by Hungarians – without any resistance. The military occupation was followed by the “takeover” of the Hungarian administration, which meant making it Romanian. The Hungarian Royal University of Ferencz József could not avoid its destiny, either: it was expropriated by military force on the 12th of May, in 1919. As the Transylvanian Hungarian remained without any independent institution of higher education, a plan occurred about foundation of an “Ecumenistic” – operated by the historical Transylvanian Hungarian Churches – university in the spring of 1920 – before signing the Trianon Treaty. This plan has failed due to the rigid resistance of the Romanian authorities, so a Reformed Teachers’ Training College was founded in the autumn of 1920. This College – also due to the chauvinist Romanian authorities – could operate only for one year.